A multi-modal probe for trace water and simultaneously monitoring lipid droplets and lysosomes. Issue 46 (9th November 2022) - Ye, Peng; Zhang, Haitao; Qu, Jianbo; Zhu, Xiuzhong; Hu, Qingfei; Ma, Shanghong
Abstract : The multimodal probe NAP-OH succeeded in trace water detection in the organic solvent and imaging of lipid droplets/lysosomes in biological cells. Abstract : Recently, multifunctional fluorescent probes have received more and more attention with the rapid development of fluorescence imaging technology. In this article, a multifunctional fluorescent probe NAP-OH was designed and synthesized. NAP-OH exhibited outstanding polarity-sensing performance and was used to detect trace water in different organic solvents by means of fluorescence emission intensity. The fluorescence spectroscopy results indicated that NAP-OH was highly responsive to trace water in acetone (LOD = 28 ppm). The co-localization experiment and cell starvation imaging showed that the probe NAP-OH could be used to distinguish lysosomes from lipid droplets, showing bright red fluorescence in lipid droplets and weak red fluorescence in lysosomes. The oleic acid stimulation experiment shows that the probe can detect the dynamic changes of lipid droplets while observing lysosomes. In addition, NAP-OH showed great photostability and low cytotoxicity and was successfully used in zebrafish imaging. Therefore, these results indicated that NAP-OH, as a multifunctional fluorescent probe, would be used in trace water detection and biological imaging.